THE ORETICAL ANALYSIS ON THE PERFORMANCE OF BRANCHED GAX CHILLER CYCLE (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
In this study, a branched GAX absorption cycle operating with NH3-H2O pair has beeninvestigated to assess its performance under steady state conditions. The cycle modeling isimplemented using Engineering Equation Solver (EES) software. Analysis includesequations of mass, species and energy conservation. The analysis is used to simulate a GAXabsorption chiller utilization for air conditioning applications with a nominal capacity of 95TR. This chiller uses solar collectors as heat source. The operating parameters are selected atdifferent values of the heat source temperature (140 - 185°C), condenser exit temperature(30 to 48°C), evaporator exit temperature (2 to 11°C) ; split ratio (0 to 0.18); the difference inammonia concentration(0.25-036), mass flow rate in solution pump mr=1 kg/s; heatexchanger effectiveness ? ? 0.8. The results showed that the average COP is sensitive tooperating conditions where the average COP and cooling capacity of the branched GAXabsorption chiller increase with increasing generator and evaporator temperature whereasthey decrease with increasing condenser temperature. Simulation results also show that thesplit ratio and ammonia concentration difference have a significant impact on theperformance of absorption chiller.